Measurement of pterygium tissue dry weight using two different tissue preparation techniques in freeze-dry method - Hilmi, Mohd Radzi; Mohd Kamal, Khairidzan; Che Azemin, Mohd Zulfaezal; Ariffin, Azrin Esmady (Universitas Islam Agung Sultan Semarang, 2019)
Introduction: The proposed freeze-dried approach for estimating pterygium dry weight closes the gap which address the possible effect of corneal compression due to pterygium on the corneal surface, translating simple laboratory procedure to a clinical practice which essential in predicting induced-corneal astigmatism. This study aim to compare an objective method in quantifying pterygium dry weight utilizing freeze-dried method via two different tissue preparation methods. Methods: 60 primary pterygium were excised using controlled partial avulsion technique performed by a single surgeon (KMK), and divided into two groups: formalin-fixed (n=30) and non-fixed (n=30). Initially, each sterile container weight was measured and 5ml of 5% buffered formaldehyde were filled and stored for 1 week for formalin-fixed group while, 5ml distilled water were filled for non-fixed pterygium group. Each container was pre-frozen for 12 hours prior to freeze-dried (- 80 ºC for 24 hours). The final product known as net pterygium tissue mass (NPTM) then weighted as dry weight. Comparative analysis of wet and dry weight, and percentage of NPTM between groups were performed via independent t-test. Results: The overall mean and SD for formalin-fixed and non-fixed pterygium wet weight were 253.33 ± 82.17 μg and 255.17 ± 63.52 μg, and dry weight were 184.92 ± 84.31 μg and 179.54 ± 72.85 μg respectively. In terms of percentage of NPTM, formalin-fixed group revealed slightly higher percentage compared to non-fixed pterygium tissue with 69.39 ± 13.29 % and 67.75 ± 13.27 % respectively. The difference of pterygium dry weight, between formalin-fixed and non-fixed pterygium tissue were statistically insignificance (P = 0.792). Conclusions: Freeze-dried method can be used to quantify the NPTM (dry weight) of pterygium fibrovascular tissue. Both methods (formalin-fixed and non-fixed) are reliable in producing results. This is proven as there is no statistical significance between the two methods.